2017
DOI: 10.1002/joc.4983
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of hourly heavy rainfall events over the Beijing metropolitan region during the warm seasons of 2007–2014

Abstract: A statistical analysis of the spatiotemporal characteristics of hourly heavy rainfall (HHR) events and rainstorm days, defined as greater than 20 mm h−1 and 50 mm day−1, respectively, is performed using observations at 5‐min intervals from 155 automated weather stations (AWSs) over the Beijing metropolitan region (BMR) during the warm seasons of 2007–2014. Results show pronounced variability in the frequencies and rainfall amounts of both HHR events and rainstorm days across the BMR of less than 150 km width f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Sun et al (2015) inferred that the complex terrain surrounding NC interferes with circulation patterns, giving rise to conditions that are conducive to extreme summer precipitation over the region. Li et al (2017) obtained that higher-(lower) frequency hourly heavy rainfall events, along with more (less) accumulated rainfall amounts, occur over Beijing's northeast mountains (west and northwest mountains), and identified the positive effect of mountain-plain circulation on the generation of the hourly heavy rainfall event in warm season. Wang et al (2014) indicated that the simulated moisture transport for a summer torrential rain case over NC was mainly influenced by the Taihang Mountain.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2015) inferred that the complex terrain surrounding NC interferes with circulation patterns, giving rise to conditions that are conducive to extreme summer precipitation over the region. Li et al (2017) obtained that higher-(lower) frequency hourly heavy rainfall events, along with more (less) accumulated rainfall amounts, occur over Beijing's northeast mountains (west and northwest mountains), and identified the positive effect of mountain-plain circulation on the generation of the hourly heavy rainfall event in warm season. Wang et al (2014) indicated that the simulated moisture transport for a summer torrential rain case over NC was mainly influenced by the Taihang Mountain.…”
Section: Introductionmentioning
confidence: 99%
“…A narrow corridor of such a water vapor transport channel in North America is known as an atmosphere river (e.g., Zhu and Newell 1998;Moore et al 2012). Sustained rainfall events require the presence of favorable quasigeostrophic forcing, frontal or orographic lifting, mesoscale cold outflow boundaries, and thermal inhomogeneity including the urban heat island effect to facilitate continuous convective initiation (Baik et al 2001;Xu et al 2012;Houze 2012;Bao and Zhang 2013;Zhong and Yang 2015;Li et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…The complex underlying terrain, comprising mountains, heterogeneous urban surfaces, and ocean, contributes to complex convective initiation (CI) processes and a variety of convection types. These convection types have drawn the attention of many researchers, who have conducted case studies and climatological analyses of these systems (Chen et al, 2012(Chen et al, , 2014Dou et al, 2015;Li et al, 2017;Meng et al, 2013;Xiao et al, 2015;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%